Karakteristik penderita tuberkulosis paru di Poli Paru RSUP Sanglah Denpasar pada bulan Januari 2016-Juli 2017 - I Putu Govinda Orna Jaya; I Made Bagiada; Pande Ketut Kurniari (DiscoverSys Inc., 2020)
Background: Tuberculosis (TB) is a global infectious disease was ranked at the second position caused died after HIV. This disease was caused by Mycobacterium tuberculosis that was attacked pulmonary organ or extrapulmonary organ. One of the countries that has a high incidence of tuberculosis is Indonesia. Indonesia was ranked at the second position as the country with the most top tuberculosis cases in the world after India.Objective: This research was aimed to know the characteristic of patients with pulmonary tuberculosis in Pulmonary Poly of RSUP Sanglah.Methods: This research was a observational descriptive study with cross-sectional approach. The subjects were 43 patients diagnosed with pulmonary tuberculosis and did the treatment in Pulmonary Poly of RSUP Sanglah from January 1, 2016 until July 31, 2017. This research is using primary data from the interview, measurement, and direct observation.Results: The results showed patients with pulmonary tuberculosis was 88.4% in productive age group; 69.8% men; educational background of subjects was 39.5% senior high school; 30.2% private employee; Socioeconomic level of 65.1% subjects was low category; 39.5%, not an active smoker; 60.5% subjects had TB contact history; 81.4% HIV negative; 95.3% subjects didn’t have DM history; 67.4% of subjects had normal body mass index; 67.4% of subjects had qualify of ventilation (large ventilation ?10%); 67.4% subjects didn’t have qualify of house humidity (humidity <40% or >70%); 55.8% subjects didn’t have qualify of house lighting (lighting <60 lux or >300 lux); 81.4% subjects had house wall which is waterproof; all of the subjects had house floor which is waterproof. Latar Belakang: Tuberkulosis (TB) merupakan penyakit infeksi global yang menduduki posisi kedua penyebab kematian setelah HIV. Penyakit ini disebabkan oleh bakteri patogen Mycobacterium tuberculosis yang menyerang organ paru atau ekstra paru seseorang. Salah satu negara yang memiliki angka kejadian tuberkulosis yang cukup tinggi adalah Indonesia. Indonesia menduduki posisi kedua sebagai negara dengan kasus TB tertinggi di dunia setelah India.Tujuan: Penelitian ini bertujuan untuk mengetahui karakteristik penderita tuberkulosis paru di Poli Paru RSUP Sanglah.Metode: Penelitian ini merupakan penelitian deskriptif observasional dengan rancangan penelitian cross sectional. Subjek penelitian adalah 43 pasien yang terdiagnosis menderita tuberkulosis paru dan melakukan pengobatan di Poli Paru RSUP Sanglah pada rentang waktu 1 Januari 2016 s.d. 31 Juli 2017. Data penelitian adalah data primer yang diperoleh dari wawancara, pengukuran, dan observasi langsung.Hasil: Hasil penelitian menunjukkan bahwa pasien TB paru terbanyak terdiri dari 88,4% memiliki usia produktif; 69,8% jenis kelamin laki-laki; 39,5% memiliki tingkat pendidikan SMA; 30,2% pegawai swasta; 65,1% berstatus sosial ekonomi kategori rendah; 39,5% bukan perokok aktif; 60,5% memiliki riwayat kontak TB; 81,4% HIV negatif; 95,3% tidak memiliki riwayat diabetes melitus; 41,8% memiliki indeks massa tubuh normal; 67,4% memiliki ventilasi rumah yang memenuhi syarat (luas ventilasi ?10%); 67,4% memiliki kelembaban rumah yang tidak memenuhi syarat (kelembaban <40% atau >70%); 55,8% memiliki pencahayaan rumah yang tidak memenuhi syarat (pencahayaan <60 lux atau >300 lux); 81,4% memiliki dinding rumah kedap air; dan seluruh pasien memiliki jenis lantai kedap air.